2016
DOI: 10.1111/hsc.12332
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of interventions that target risk factors for elder abuse

Abstract: What is known about this topic• Elder abuse is an important public health and societal problem which requires a response from both the primary healthcare and social service sectors.• Current knowledge about the effectiveness of many of these approaches is limited.• There is a need to identify evidence-based interventions. What this paper adds• Identifies a body of empirical research that evaluates prevention interventions.• No accounts of multi-modal interventions addressing key risk factors at the level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
(25 reference statements)
1
20
0
3
Order By: Relevance
“…The issue of drug use and its association with risky sexual behaviors is a multifaceted issue that requires the intervention of experts in various fields and institutions, and intra-organizational planning alone is not sufficient for a comprehensive look at it [25][26][27]. The focus of the present study is on two major issues: first, the issue of drug use among women that, according to reports, is increasing as quickly as it is increasing among men [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of drug use and its association with risky sexual behaviors is a multifaceted issue that requires the intervention of experts in various fields and institutions, and intra-organizational planning alone is not sufficient for a comprehensive look at it [25][26][27]. The focus of the present study is on two major issues: first, the issue of drug use among women that, according to reports, is increasing as quickly as it is increasing among men [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…29 5.4 | Solution suggestions for preventing the neglect and abuse of the participants Almost all of the participants stated that elderly people over 75 years old, those living alone, those not able to meet their own needs and those with psychiatric disorders are exposed to more neglect and abuse. In the literature, being 75 years old or older, 24,30,31 living alone, having a physical or mental disability 24,32 and having a psychiatric disorder 33 have been emphasized as the factors that increase the risk of elder neglect and abuse. In this study, it was found that almost all of the students knew the risk factors.…”
Section: Participants' Experiences and Reactions To Neglect Abuse Omentioning
confidence: 99%
“…An intervention based on a public health model aimed at preventing elder abuse should operate at the levels of primary, secondary and tertiary interventions: primary interventions target the whole population victim of elder abuse to prevent elder abuse; secondary interventions focus on early identifying and stopping the occurrence of elder abuse; tertiary interventions target elderly people who are victims of abuse and focus on preventing the recurrence of abuse (11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased visibility of this subject in recent decades, scientific production remains deficient, particularly with respect to studies on interventions to prevent elder abuse (11) . In addition to the limited data on preventionoriented interventions (13) , few interventions are based on scientifically grounded hypotheses and have had their efficacy and effectiveness measured (14) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation